Prophylactic Efficacy of Tibial Plateau Levelling Osteotomy for a Canine Model with Experimentally Induced Degeneration of the Cranial Cruciate Ligament - Shimada, Masakazu; Kanno, Nobuo; Ichinohe, Tom; Suzuki, Shuji; Harada, Yasuji; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to clarify the histological effects of tibial plateau levelling osteotomy on cranial cruciate ligament degeneration induced by excessive tibial plateau angle.Study Design Five female Beagles were used to bilaterally create excessive tibial plateau angle models surgically. A second tibial plateau levelling osteotomy was performed 11 months after the first surgery on the right stifle (tibial plateau levelling osteotomy group), and a sham operation that did not change the tibial plateau angle was performed on the left stifle (excessive tibial plateau angle group). At 6 months after the second surgery, the dogs were euthanatized. The cranial cruciate ligament was stained with haematoxylin–eosin to assess the cell density, Alcian-Blue to assess proteoglycans and Elastica-Eosin to assess elastic fibres, and immunohistochemically stained to assess type I (COL1) and type II collagen and SRY-type HMG box 9 (SOX9) expression.Results In each group, the cranial cruciate ligament degeneration, especially on the tibial side, including the presence of Alcian-Blue- and Elastica-Eosin-positive regions, decreased in COL1-positive regions, and enhancement of SOX9 expression was observed. Besides, compared with the tibial plateau levelling osteotomy group, the excessive tibial plateau angle group showed increases in Alcian-Blue- and Elastica-Eosin-positive regions and a decrease in the COL1-positive regions.Conclusion The results suggested that excessive tibial plateau angle-induced cranial cruciate ligament degeneration can be suppressed by reducing the biomechanical load on the cranial cruciate ligament by performing tibial plateau levelling osteotomy.
Keywords: chondrometaplasia; cruciate ligament disease; dog; excessive tibial plateau angle; tibial plateau levelling osteotomy